Annotated checklist of the rotifers (Phylum Rotifera), with notes on nomenclature, taxonomy and distribution - Segers, Hendrik (Zootaxa, 2007)
Phylum Rotifera comprises about 2030 known species classified in three main groups, the marine Seisonida (3 species), the Monogononta (1570 species) and the unique, exclusively parthenogenetic Bdelloidea with 461 clonal species. Here I present an annotated checklist of the taxon, giving the global distribution of the valid species. This checklist contains over 3,000 available names at the genusand species-group level, including valid names and a non-comprehensive list of synonyms. A number of taxonomic and nomenclatural suggestions following from the review is presented. Suggestions include several new synonyms and two nomina nova: Dissotrocha kostei for Dissotrocha aculeata Koste, 1996 non Ehrenberg, 1838 (stat. nov., ex. Dissotrocha hertzogi aculeata) and Lepadella zigzag for Lepadella bractea Myers, 1934 non (Ehrenberg, 1838). This contribution also describes features of an on-line, global names database of the Rotifera, on which this checklist is based.